I don$1 (Bt want to take a bath! s - Sykes, Julie; Warnes, Tim (Wauwatosa, Wis. : Little Tiger Press, 1997)
Even though all of his jungle friends take baths, Little Tiger decides he doesn$1 (Bt need one, until one day he sees his reflection in the river.s
Keywords: Baths -- Fiction; Jungle animals -- Fiction; Tigers -- Fiction